The Effect of Leadership Style and Organizational Culture on Performance of Plantation Public Company Employees: The Role of Job Satisfaction as an Intervening Variable - Tannady, Hendy; Purnamaningsih Purnamaningsih; Naila Zaneta Ristyova (HM Publisher, 2023)
The human component (human resources) is the most important factor in management because of its importance in carrying out organizational policy and operational tasks. Human resources (HR) are people who serve as the backbone of organizations, including both institutions and businesses and who act as resources that need to be developed. Human resources are the key to determining the development of the organization. Hence they are included as a highly significant aspect. This study's objective was to determine and assess the effects of organisational culture and leadership style on employee performance, as shown by job satisfaction. This study's quantitative methodology employs a survey assessment method. The sampling technique used in this investigation was purposeful sampling. 34 individuals made up the study's sample. The tool for gathering data makes use of a questionnaire. The data analysis method used in this inquiry is partial least squares. Employee performance is highly influenced by leadership style, organisational culture, work satisfaction, and job satisfaction as intervening variables.